Smart curtain / Muhammad Faizzuddein Mazlan, Zakiaria Sehat @ Ishak and Ubaidillah Rosli - Mazlan, Muhammad Faizzuddein; Sehat @ Ishak, Zakiaria; Rosli, Ubaidillah (2013)
Due to the recent technology, there is a need in the level of the security to be upgraded. This includes the security in workplace, home, bank, shops and government building. SMART curtain is an innovation project that will implemented automation in daily life. This project has two LDR sensors. The LDR and the rest of the components are controlled by IC LM358. This component acts as brain in the circuit. LDR acts when the intensity of the light is changed and the result will be motor that moves the curtain. This project use 9 volts DC Power supply which is regulated through the regulator circuitThe system operate when user switch on the circuit. With light the curtain will move to the right and with dark the curtain will move to the left. When switch is turn off the circuit will break.